TRANSFORMASI PEMBELAJARAN MENUJU MERDEKA BELAJAR KAMPUS MERDEKA: DITINJAU DARI PERSEPSI PEMINATAN MAHASISWA DAN MANFAAT PROGRAM MBKM - Sri Opti; Nurul Aisyah Rachmawati (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2022)
The purposes of this study are to analyze the students perception of interest and the benefit of the MBKM program. This study uses primary data obtained from survey results to students of the Accounting Study Program, Universitas Trilogi Jakarta. Data were analyzed using descriptive qualitative method. The results showed that the top three of MBKM activities that students were interested in were: 1) Internships/work practices; 2) Student exchange; and 3) Entrepreneurial activities. The results also show that the benefits felt by students in the MBKM program are quite large. Based on these results, leaders at both the faculty and university levels should focus more on facilitating and developing these three forms of activity, one of which is by establishing more collaboration with related parties. Thus, the implementation of the MBKM program becomes more optimal.